DYNAMIC RBI WITH CENTRAL DIFFERENCE METHOD APPROACH IN CALCULATION OF UNIFORM CORROSION RATE: A CASESTUDY ON GAS PIPELINES - Alviansyah, M.Riefqi Dwi; Hartoyo, Fernanda; Nurullia, Zahra Nadia; Kurniawan, Ari (UI Scholars Hub, 2022)
The oil and gas industry generally uses a piping system to drain fluids. Even though the pipes used have been well designed, the use of pipes as a means of fluid transportation still provides the possibility of failure that can occur at any time, one of which is due to uniform corrosion. The use of standard Risk Based Inspection (RBI) according to the API RBI 581 document has been widely used to anticipate potential failures to pipe components. The use of standard RBI can reduce the risk of failure significantly. Because the standard RBI considers the component risk value to be constant, it causes an error in the component status assessment. It is unfortunate happen, if an industry fails due to an error in the inspection results, causing financial losses. This research will design dynamic RBI using thickness data of 12 PT.X inspection points in 5 inspection time intervals. The results showed that the dynamic RBI design that was compiled could provide real-time component condition status, capture fluctuations in the corrosion rate that occurred, and provide an accurate description of the actual component condition. RBI design makes inspection and maintenance planning more precise by reducing the frequency of redundant inspections and the possibility of inspection planning errors.